2020
DOI: 10.1007/s11368-020-02760-7
|View full text |Cite
|
Sign up to set email alerts
|

Using 137Cs and 210Pbex to trace soil erosion rates for a small catchment in the mid-hills of Nepal

Abstract: Purpose Soil erosion is a major threat to agricultural sustainability in the hills of Nepal. However, little is known about the soil erosion rates at a small catchment scale in this region. Materials and methods In this study, the soil redistribution rates in a typical small hilly catchment in the Ramechhap District of Nepal were evaluated using the 137 Cs and 210 Pb ex tracer techniques. Nine representative slopes under three land uses and a reference site from the gentle sloping forest land within the catchm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 62 publications
2
7
0
Order By: Relevance
“…The gross annual SL of the watershed was estimated to be 2,307,144 t/year with a mean value of 31 t/ha/year. Similar to the current finding, a mean SLR of 31.29 t/ha/year has been reported by Yuan et al (2020), in the mid-hill regions of the Koshi basin, Nepal. However, the rate of our study finding was quite higher than the tolerable SLR (15 t/ha/ year) in the Himalayan region (Ban et al 2016).…”
Section: Annual Soil Erosion Rate and Its Spatial Distributionsupporting
confidence: 91%
See 1 more Smart Citation
“…The gross annual SL of the watershed was estimated to be 2,307,144 t/year with a mean value of 31 t/ha/year. Similar to the current finding, a mean SLR of 31.29 t/ha/year has been reported by Yuan et al (2020), in the mid-hill regions of the Koshi basin, Nepal. However, the rate of our study finding was quite higher than the tolerable SLR (15 t/ha/ year) in the Himalayan region (Ban et al 2016).…”
Section: Annual Soil Erosion Rate and Its Spatial Distributionsupporting
confidence: 91%
“…Various research have been conducted in a range of spatial scales in the Koshi River Basin (KRB), related to this thematic area in the last few decades (Santosh et al 2014;Uddin et al 2016;Kafle et al 2017;Mishra et al 2019;Sinha et al 2019;Yuan et al 2020). These studies have mainly focused on the river morphology/landform dynamics, rate of soil loss (SL), sediment connectivity, and the implication of sediment dynamics for flood hazards and their consequences.…”
Section: Introductionmentioning
confidence: 99%
“…The 210 Pb ex reference inventories ranging from 3637 to 5983 BqÁm À2 have been reported for an alpine meadow land of the Xinhai Basin in the eastern TP (Hu & Ma, 2022), and values ranged from 2612 to 7377 BqÁm À2 for grassland in the Yangtze, Yellow and Lancang rivers of TP (Li et al, 2019). Yuan et al (2021) reported that the 210 Pb ex reference inventory of 17 876.9 BqÁm À2 in the mid-hills of Nepal, which is higher than the inventory in this study, mainly due to the high mean annual precipitation (1315 mm). The 137 Cs reference value of 385.26 BqÁm À2 is consistent with those reported in adjacent areas when corrected for the sampling year (2020) and the 210 Pb ex reference value in this study falls within the range of adjacent areas, the inventory of 210 Pb ex in this study was tested to be 6485.56 BqÁm À2 .…”
Section: Changes On Vegetation Coverage In Sand Source Area and Its R...mentioning
confidence: 95%
“…The depth distribution of the 137 Cs and 210 Pb ex for the reference site (Figure 2) showed that the surface horizon had the maximum concentrations of both radionuclides, which is typical of an undisturbed site (Gaspar & Navas, 2013;Yuan et al, 2021). The coefficient for the 137 Cs depth distribution shape was calculated to be 0.14 cm À1 , which is a crucial parameter in the profile shape model (Equation ( 2)) for evaluating soil erosion rates on fencing land and grazing land.…”
Section: Changes On Vegetation Coverage In Sand Source Area and Its R...mentioning
confidence: 99%
“…More effective erosion monitoring methods are tracer methods (i.e. 137 Cs, 210 Pb, and 10 Be) (Gaspar et al, 2013;Porto et al, 2014;Yuan et al, 2020), RTK-GPS instruments (Wu & Cheng, 2005;Cheng et al, 2007;Zhang et al, 2011;Castillo et al, 2014), LiDAR and photogrammetry by Drone (Hout et al, 2020;Tak et al, 2020), and 3D laser scanners (Haubrock et al, 2009). In this context, pedometric such as magnetic susceptibility (MS) methods emerged to predict specific soil properties such as soil organic carbon using mass-specific susceptibility at low frequency (Jakšík et al, 2016).…”
Section: Introductionmentioning
confidence: 99%